Economic Freedom, Globalization and Quality of Life in Asia: Comparison based on Income Level - Awan, Asma; Mansab, Fozia; Bashir, Furrukh (Pakistan Journal of Humanities and Social Sciences, 2022)
This study empirically estimates the impact of economic freedom and Globalization on the quality of life in Asia disaggregated by income level. Balanced panel data have been used in this study that covers the time period of 2000-2021. The IPS panel unit root test is applied for the stationarity of the variables that show mixed order of integration so the panel ARDL technique is utilized. With respect to Lower Middle-Income Countries, we found that economic freedom, globalization, and official development assistance have a positive impact on quality of life, while development expenditure and remittances showed negative results on quality of life in the long run. With respect to Upper Middle-Income Countries, economic freedom, remittances, and official development assistance showed negative results while globalization and development expenditures showed positive impacts on quality of life in the long run. With respect to High-Income Countries, economic freedom, globalization, and development expenditures showed positive impacts while remittances had an inverse effect on the quality of life over a longer period of time. Therefore, it is suggested to improve the situation of Economic freedom in Lower Middle and High-Income countries while there is a need to improve the situation of institutional quality in Upper Middle-Income Countries.